1990
DOI: 10.1111/j.1471-4159.1990.tb13276.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Thyrotropin‐Releasing Hormone and Luteinising Hormone‐Releasing Hormone by Enzymes of Brain Tissue

Abstract: In this article, the enzymes of brain and associated tissues that can degrade thyrotropin-releasing hormone (TRH) and luteinising hormone-releasing hormone (LH-RH) are reviewed. As both TRH and LH-RH are considered to act as neurotransmitters or neuromodulators in the CNS, attention is paid to the subcellular location of the enzymes described and how their topographies and substrate specificities fit them to playing roles as inactivating agents for TRH and LH-RH or as regulators of intracellular concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 126 publications
4
47
0
Order By: Relevance
“…CAP and PAP-I were activated by DTT, a thiol-reducing agent, characterizing them as sulphydryldependent peptidases. DTT is an activator of the type I PAP and an inhibitor of the type II (O'Cuinn et al 1990), and the degradation of FPP (possible substrate of PAP-I) is also increased by the presence of DTT (Cockle et al 1994), which confirms that PAP-I is among the enzymes studied in the present work and FPP is one of its substrates. Overall, the present results show that seminal peptidase activities of C. d. terrificus have distinct biochemical properties, and therefore it is possible to attribute them to different proteins.…”
Section: Rattlesnake Seminal Peptidasessupporting
confidence: 66%
“…CAP and PAP-I were activated by DTT, a thiol-reducing agent, characterizing them as sulphydryldependent peptidases. DTT is an activator of the type I PAP and an inhibitor of the type II (O'Cuinn et al 1990), and the degradation of FPP (possible substrate of PAP-I) is also increased by the presence of DTT (Cockle et al 1994), which confirms that PAP-I is among the enzymes studied in the present work and FPP is one of its substrates. Overall, the present results show that seminal peptidase activities of C. d. terrificus have distinct biochemical properties, and therefore it is possible to attribute them to different proteins.…”
Section: Rattlesnake Seminal Peptidasessupporting
confidence: 66%
“…3.4.19.3), the pyroglutamylhistidine bond. However, these soluble enzymes do not control intracellular TRH levels in vivo because TRH is stored inside secretory granules (O'Cuinn et al 1990, Joseph-Bravo et al 1998. A different pyroglutamyl peptidase was initially detected in serum and termed thyroliberinase because of its strict specificity for TRH (Bauer & Nowak 1979).…”
Section: Inactivationmentioning
confidence: 99%
“…All the TRH mediated metabolites other than unknown metabolite(s) were consistent with those reported previously. 2,11) Immunoblot Analysis Male F344/DuCrj rat liver, kidney and brain cytosolic or microsomal fractions and a polyclonal antibody raised against rat PAP-I in rabbits were prepared as previously described. 13) SDS-PAGE analysis of denatured samples (7-28 mg protein) was performed on 12.5% gels according to the method of Laemmli.…”
Section: )mentioning
confidence: 99%
“…1,11) Nevertheless, the contribution of cytosolic PAP-I to the hydrolysis of TRH in vivo is controversial. Charli et al 6) reported that pGlu diazomethyl ketone, a PAP-I inhibitor, did not enhance TRH levels in the brain in vivo or in vitro, but Faivre-Bauman et al 12) observed increased levels of TRH when primary cultures of hypothalamic cells were treated with Z-Gly-ProCHN 2 , also known as a PAP-I inhibitor.…”
mentioning
confidence: 99%